Morbidly adherent placenta: management is real challenge - Vyas, Rupa C.; Patel, PrinceNrutik Amrut; Shah, Sapana; Vala, Shweta N.; Patel, Nidhi B. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: The objective of the present study was to describe management of morbidly adherent placenta with placenta previa and feto-maternal outcome. Methods: All antenatal USG diagnosed cases of morbidly adherent placenta were analyzed. The cases were managed by elective caesarean hysterectomy and non-separation of placenta at delivery. Amount of blood loss, blood transfused, ICU admission, postnatal complications and hospital stay was recorded. Results: From January 2010 to October 2018, 22 cases of morbidly adherent placenta were diagnosed on gray scale and color Doppler during antenatal ultrasound scan. Scheduled caesarean hysterectomy without attempting placental removal was done. Subtotal hysterectomy was performed in 17(77.2%) cases and total hysterectomy in remaining 5(22.8%) cases. All the patients required blood transfusion. Seven (31.8%) patients had urinary bladder injury. One case developed DIC and One needed ventilatory support. No patient died in this series. Conclusions: Antenatal diagnosed cases of morbidly adherent placenta, avoidance of placental separation and caesarean hysterectomy results in better maternal outcome.